Descriptions of diabetes burnout from individuals with Type 1 diabetes: an analysis of YouTube videos. Issue 8 (4th July 2019) - Abdoli, S.; Hessler, D.; Vora, A.; Smither, B.; Stuckey, H.
Abstract: Aim: The purpose of the study was to analyse self‐descriptions of diabetes burnout in individuals with Type 1 diabetes via YouTube videos. Methods: In this qualitative descriptive study, a systematic approach was used to search YouTube videos with a title, description or content specifically about diabetes burnout dated between 2007 and 2017. Irrelevant or duplicated videos were excluded using eligibility criteria. All videos meeting inclusion criteria ( n = 32) from individuals with Type 1 diabetes were transcribed verbatim and analysed using a qualitative content analysis approach. Descriptive statistics were used to analyse video characteristics. Results: The four major themes associated with diabetes burnout were: (i) feeling mentally drained and physically tired of dealing with self‐care; (ii) experiencing a detachment from self, diabetes care and support system; (iii) being powerless and paralysed to 'climb out' of diabetes burnout; and (iv) contributing potential factors to diabetes burnout. Conclusions: Self‐descriptions of diabetes burnout suggest that it is a combination of emotions and behaviours on a spectrum from exhaustion to detachment accompanied by an overwhelming sense of powerlessness. More studies are needed to further clarify diabetes burnout and its distinction from, or overlap with, other related psychosocial concepts in diabetes care. What's new: This is the first study on diabetes burnout using YouTube videos from individuals with Type 1 diabetes. The study identifies diabetes burnout as exhaustion, detachment and powerlessness, which is similar to the most widely accepted conceptualization of occupational burnout. Results suggest preliminary support for a linear relationship between diabetes distress and burnout in which distress results in burnout.